Escritura e contexto amazônico: diferentes formas de arquivo do povo Tikuna - Anastácio (Dauamücü), Tiago Berezinho (2019)
The theme of this dissertation is scripture and the Amazonian context, and it focuses on the types of archives of the Tikuna people, in particular the set of sculpted and perforated objects (ügümüane) and the set of woven objects (mugümüane), for their importance, their symbolic role and sense of meaning in the historical context in which the Tikuna people started an important process of struggle for the demarcation of their land. The author’s main goal, as a member of the Tikuna people, is to reposition the study of material objects of an oral society to a type of socially and historically constituted archive, as well as study the types of archives of the Tikuna people, who are scattered through three countries (Brazil, Peru, and Colombia), and is the largest group in the Brazilian Amazon. To reach this goal, a variety of craft works are presented, which correspond to different objects in the context of their production. Information was gathered in the course of studies on the material part of traditional Tikuna culture, through field research and an extensive survey of ethnographic collections at the Museu Magüta in Benjamin Constant (Amazon state, Brazil). The hypothesis is that the power to select and cut what may constitute a Tikuna Archive comes from a greater constituent power that surpasses the physical archives and spreads throughout the Tikuna society. In an attempt to prove it, the author deals with categorized objects in native terms, whilst turning his attention to oral tradition and memory in an oral society, paving the way to further studies on the importance of memory in an oral tradition and its importance in a written culture.